EFEKTIVITAS PENGGUNAAN MEDIA BAHAN ALAM TERHADAP KEMAMPUAN MENGENAL HURUF ANAK DI PAUD PERMATA BUNDA KOTA SUBULUSSALAM: THE EFFECTIVENESS OF USING NATURAL MATERIALS AS LEARNING MEDIA ON CHILDREN’S LETTER RECOGNITION ABILITY AT PERMATA BUNDA EARLY CHILDHOOD EDUCATION CENTER, SUBULUSSALAM CITY - Faridy, Faizatul; Amelia, Lina; Fatiyyah, Asna Khoiril (Universitas Islam Malang, 2024)
Children can learn to recognise words by use of media. The media made from natural resources. According to the findings of the observations, children in class B at PAUD Permata Bunda Kota Subulussalam were still developing their alphabet recognition skills. The purpose of this study is to ascertain how well children at PAUD Permata Bunda in Subulussalam City can recognise alphabet when exposed to natural media. This study used a pretest-posttest design with a single group and a pre-experimental methodology. Total sampling was the method used for class B, which consisted of 24 kids in total. Sheets for documentation and observation are used as data gathering tools. Normality tests, t-tests, and hypothesis testing are among the data analysis methods employed. The average pretest score increased from 2.1 to 3.0 in the posttest, indicating that the usage of natural media is beneficial in enhancing children's words recognition skills at PAUD Permata Bunda, Subulussalam City. Ha is accepted and Ho is rejected based on hypothesis testing, which reveals that the value of tcount (29.038) > ttable (2.068), indicating that the usage of natural material media is effective on children's capacity to recognise letters in PAUD Permata Bunda, Subulussalam City. It may be concluded that children at PAUD Permata Bunda, Subulussalam City, who are between the ages of five and six, benefit from media made from natural materials in terms of their capacity to recognise letters.